The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/membranes12090833
|View full text |Cite
|
Sign up to set email alerts
|

pH and pCl Operational Parameters in Some Metallic Ions Separation with Composite Chitosan/Sulfonated Polyether Ether Ketone/Polypropylene Hollow Fibers Membranes

Abstract: The development of new composite membranes is required to separate chemical species from aggressive environments without using corrective reagents. One such case is represented by the high hydrochloric acid mixture (very low pH and pCl) that contains mixed metal ions, or that of copper, cadmium, zinc and lead ions in a binary mixture (Cu–Zn and Cd–Pb) or quaternary mixture. This paper presents the obtaining of a composite membrane chitosan (Chi)–sulfonated poly (ether ether ketone) (sPEEK)–polypropylene hollow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…For the first challenge, which in our previous studies was only partially solved by using sulfonated polyether–ether–ketones [ 52 , 56 ], a resistant polymer with strongly acidic ionic groups sulfonated ethylene-propylene-diene terpolymer was used (sEPDM), which, as shown in Figure 5 and Figure 6 , was beneficial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first challenge, which in our previous studies was only partially solved by using sulfonated polyether–ether–ketones [ 52 , 56 ], a resistant polymer with strongly acidic ionic groups sulfonated ethylene-propylene-diene terpolymer was used (sEPDM), which, as shown in Figure 5 and Figure 6 , was beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan-ionic polymer composite membranes have recently been used as essential elements in fuel cells [ 51 ] and in the separation of certain metal ions [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…If we focus on membrane processes, it can be stated that the membrane is a window of a multi-component system ( Figure 5 ), with selective permeability for chemical species of the system [ 173 ]. This membrane allows the separation of the considered system, consisting of a continuous phase (solvent) in which ionic chemical species, molecules and macromolecules are dissolved.…”
Section: Membrane and Membrane Processesmentioning
confidence: 99%
“…The representative ways of delivery, controlled release of the various chemical species of interest, many of which have been studied for melatonin as well, are suggested in Figure 1 [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies related to improving the performance of fuel cell membranes have shown that an effective means of chitosan reticulation can be performed with ionophores with sulfonic groups of the polyether–ether sulfonated ketone type [ 40 ].…”
Section: Introductionmentioning
confidence: 99%